If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x-(6+7)=7x-23
We simplify the equation to the form, which is simple to understand
4x-(6+7)=7x-23
Simplifying terms in parentheses
4x-(+13)=7x-23
Remove unnecessary parentheses
4x-13=7x-23
We move all terms containing x to the left and all other terms to the right.
+4x-7x=-23+13
We simplify left and right side of the equation.
-3x=-10
We divide both sides of the equation by -3 to get x.
x=3.33333333333
| xy=a-b | | 5.8(3+3x)-3.4=14 | | (-10.3)+(-0.08)x=-4.7 | | (2n+2)-(-3n+3)= | | (1-3x)-(8-10x)= | | 19+2g=-17g-15+2g | | 4+a=15 | | 3000-20%= | | (-3n+(-6))-(-5n+2)= | | 5(3)=10y+20 | | 16(-10-19y)+15y= | | 8-4+8= | | 2(+4)+6=22 | | 31x+115=84 | | -4x-44+x=31 | | 8(x-8)-2(x-1)+5x= | | x-4+8=12 | | -7c-5=c-373 | | -3y-12=-9(3) | | -x-10x-76=89 | | 2x+x=6.30 | | -6t+20=4t-20-5t | | 2+2b+bh+1h=a | | -x^2+254x=0 | | -116+12x-x=38 | | 310+n=200 | | 20x-300x^2=0 | | 48=15 | | 12y+36=4(9+3y) | | 1(3-x)=10(3-2x) | | x+2.7=5.6 | | 8h+4=h-311 |